CLINICAL AND PSYCHOPATHOLOGICAL FEATURES OF POST-STRESS DISORDERS IN PERSONS WITH HOSTILITIES EXPERIENCE - Kozhyna, H.M.; Skrypnikov, A.M.; Druz, O.V.; Zelenska, K.O.; Chernenko, I.O. (World of Medicine and Biology, 2021)
Hostilities is a major cause of combat mental trauma, the development of acute stress and post-traumatic stress disorder, and has a significant impact on the individual. The continuity of war actions in eastern Ukraine is the reason why servicemen are in a multifactorial state of stress, the extreme forms of which are mental changes and disorders. At the same time, the more soldiers experience intense forms of combat stress, the more psychological losses are suffered by units of the Armed Forces of Ukraine. According to the results of the study, all examined patients have the consequences of combat stress, which determines the specifics of the clinical picture of post-stress disorders. The clinical structure of post-stress disorders in the examined patients was represented by: moderate or severe depressive episode without psychotic symptoms (F 32.1, F 32.2) – 14.5 % of the examined group I and 24.2 % group II; anxiety disorders (F 41.0, F 41.1) – 18.4 % and 26.1 %, respectively; post-traumatic stress disorder (F 43.1) – 32.1 % and 28.8 %, respectively; adjustment disorders (F 43.2) – 35.0 % of patients from group I and 20.9 % – from group II.
Keywords: post-traumatic stress disorder; post-stress disorders; combatants; hostilities; mental disorders; volunteers